Digitalizace Prostorových Objektů Pomocí Výpočetní Tomografie S Rekonstrukcí Na 3D Tiskárně - Kolomazníková, Helena (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
The tomograph prototype based on visible light is devised and built in this paper. The propose of software for object scanning and data evaluation was included too. The principles of medical tomographs were used for prototype designing.
Keywords: CT systems; tomograph prototype; Arduino; Octave